Pediatric Acute-Onset Neuropsychiatric Syndrome (PANS) and Occupational Performance: A Scoping Review. - Newby, Michelle J.; Haracz, Kirsti; Lane, Shelly J.; Tona, Janice (American Journal of Occupational Therapy)
Importance: Pediatric acute-onset neuropsychiatric syndrome (PANS) is a neuroimmune condition that significantly affects children's occupational performance across multiple domains. However, occupational performance is often overlooked in current PANS clinical frameworks, despite its critical role in daily functioning and well-being. Objective: To synthesize evidence on the occupational performance challenges experienced by children with PANS, the tools used to assess these challenges, and occupational therapy interventions used with these children. Data Sources: MEDLINE, CINAHL, Cochrane Library, PsycINFO, SCOPUS, ERIC, and EMBASE were searched from their inception through May 17, 2024. Study Selection and Data Collection: Peer-reviewed studies addressing PANS and occupational performance were included, with data categorized using the Occupational Therapy Practice Framework, 4th Edition. Findings: Of 3,431 records, 40 studies met inclusion criteria. Occupational performance challenges centered on communication, nutrition, education, rest/sleep, social participation, and toileting, with limited data on bathing, dressing, personal hygiene, and play and leisure. Assessments emphasized client factors, rarely using occupation-based tools. Only 2 studies mentioned occupational therapy interventions. Conclusions and Relevance: PANS has a pervasive impact on children's occupational performance, highlighting the urgent need to prioritize it within clinical frameworks. Future research should focus on occupation-based intervention studies and assessments to enhance outcomes for children with PANS. Plain-Language Summary: Pediatric acute-onset neuropsychiatric syndrome (PANS) causes sudden, severe symptoms, such as obsessive-compulsive behaviors, eating difficulties, sensory and motor changes, and developmental regression, which significantly disrupt children's ability to perform daily activities. This study included 40 research articles addressing what is known about the impact of PANS on children's daily functioning and the role of occupational therapy in managing challenges. Results showed that most studies focused on communication, nutrition, education, sleep, social, and toileting challenges, but few addressed other daily tasks like bathing, dressing, personal hygiene, and play or leisure. Despite identified challenges, only two studies mentioned occupational therapy interventions, highlighting a major gap in the evidence. Assessments focused mainly on a child's skills and challenges, rather than looking at how the child participates in everyday activities. The findings highlight the need to better understand the challenges children with PANS face in their everyday activities and to provide practical strategies to help them succeed. Positionality Statement: Newby is a pediatric occupational therapist and researcher with both professional and personal experience of PANS. Her clinical work with children diagnosed with PANS, along with personal experience supporting a family member with this condition, has deepened her interest in the episodic fluctuations in occupational performance that occur during periods of exacerbation and remission. Haracz is an occupational therapist, academic, and researcher with a focus on mental health and the intersection between physical and psychological well-being. Lane is an occupational therapist, academic, and researcher who specializes in the neuroscience of developmental conditions and how sensory processing differences affect children's engagement in daily occupations. Tona is an occupational therapist and educational psychologist whose interest in neuroinflammatory disorders emerged following a family member's diagnosis with PANS. Her research explores the characteristics of PANS, treatment access, caregiver burden, and the role of occupational therapy in improving participation in both PANS and long-COVID populations. This review included research articles addressing what is known about the impact of pediatric acute-onset neuropsychiatric syndrome (PANS) on children's daily functioning and the role of occupational therapy in managing challenges.